Five new species of the spider genus Savarna Huber, 2005 (Araneae: Pholcidae) from Thailand - Lan, Tianqi; Yao, Zhiyuan; Zheng, Guo; Wongprom, Prasit; Li, Shuqiang (Zootaxa, 2020)
The genus Savarna Huber, 2005 comprises only five species, from southern Thailand, Peninsular Malaysia and Sumatra. In this study, five new species are described from Thailand: Savarna bannang sp. nov. (Yala), S. chiangmai sp. nov. (Chiangmai), S. huahin sp. nov. (Prachuap Kiri Khan), S. satun sp. nov. (Satun), S. thungsong sp. nov. (Nakhon Srithammarat). All new species are described from males and females. The distribution of S. chiangmai sp. nov. represent the northernmost record of the genus.